Sistem Penyerbukan Kelapa Genjah Salak (Cocos nucifera L.) - MIFTAHORRACHMAN, MIFTAHORRACHMAN (Pusat Penelitian dan Pengembangan Perkebunan, 2010)
Pollination System of Salak Dwarf Coconut (Cocos nucifera L.)The research was conducted to know pollination system of Salak Dwarf coconut that could be applied on breeding program of Salak Dwarf. Four treatments had tested on twenty-nine old Salak Dwarf population at Kima Atas Experimental Garden, Manado, North Sulawesi. The treatments tested are: (A) inflorescence has bagged without emasculating male flowers; (B) inflorescence has bagged with emasculating male flowers; (C) withouth bagging of inflorescence with emasculating male flowers; (D) control, without bagging of inflorescence and without emasculating male flowers. Difference of the treatments were analyzed by analysis of variance and Honestly Significant Difference test (HSD). The result showed that treatments of A and B significant different with C and D, while C and D have no difference. Observation of two-month fruit set showed that the treatment of B has smallest percentage of fruit set (2.48%). It means that pollination system of Salak Dwarf tend to out cross.